Intensi Whistleblowing Mahasiswa dan Profesional Akuntansi: Aplikasi Theory Planned of Behavior - Wuryaningsih, Wuryaningsih; Dzulhasni, Sahilly (E-Jurnal Akuntansi, 2022)
This study aims to examine the factors in the Theory Planned of Behavior (TPB) on the whistleblowing intentions of students and accounting professionals. The study used an online survey method with a sample of 142, 84 were accounting students and 58 were accounting professionals. In addition, the study also compares whistleblowing intentions between accounting students and accounting professionals. Research data were analyzed using path analysis (SEM-PLS). The results showed that subjective norms were a strong factor in predicting the whistleblowing intentions of accounting students and accounting professionals both through internal and external channels, while attitudes towards whistleblowing were only proven through internal channels, and not proven for external channels. Furthermore, perceived behavioral control has a significant effect on whistleblowing intentions through external channels and has no effect on internal channels. In addition, there were no differences in whistleblowing intentions between students and accounting professionals through internal channels, but there were differences in whistleblowing intentions between the two groups through external channels. Keywords: Whistleblowing Intention, Accounting Students, Accounting Professionals, Theory Planned of Behavior.